2016
DOI: 10.1371/journal.pone.0151029
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Nitric Oxide on Bothropoides insularis Venom Biological Effects on Murine Macrophages In Vitro

Abstract: Viperidae venom has several local and systemic effects, such as pain, edema, inflammation, kidney failure and coagulopathy. Additionally, bothropic venom and its isolated components directly interfere on cellular metabolism, causing alterations such as cell death and proliferation. Inflammatory cells are particularly involved in pathological envenomation mechanisms due to their capacity of releasing many mediators, such as nitric oxide (NO). NO has many effects on cell viability and it is associated to the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
2
1
0
Order By: Relevance
“…Toxicity induced by snake peptides, as for many other molecules, may have variations on the molecular, cell, tissue, organ, and organism levels. Metabolic alterations and oxidative stress increase, , cell death by apoptosis, , and necrosis are all mechanisms of action observed in similar studies.…”
Section: Resultssupporting
confidence: 68%
“…Toxicity induced by snake peptides, as for many other molecules, may have variations on the molecular, cell, tissue, organ, and organism levels. Metabolic alterations and oxidative stress increase, , cell death by apoptosis, , and necrosis are all mechanisms of action observed in similar studies.…”
Section: Resultssupporting
confidence: 68%
“…Inflammation plays an important role in the development of snake venom toxicity. BinsV was previously described as its inflammatory effect (Menezes et al, 2016), and in this work we observed the accumulation of inflammatory cells on kidney of mice treated with BinsV.…”
Section: Resultssupporting
confidence: 68%
“…Cell viability was assessed as described by De Menezes et al. (), using MTT (3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide) assay. Briefly, the cells were seeded in 96‐well plates at density of 5 × 10 3 cells/well (A549 and HCT8) and 2 × 10 3 cells/well (IMR90).…”
Section: Methodsmentioning
confidence: 99%